2012
DOI: 10.5014/ajot.2012.004168
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Processing, Problem Behavior, Adaptive Behavior, and Cognition in Preschool Children With Autism Spectrum Disorders

Abstract: OBJECTIVE. This retrospective study explored sensory processing characteristics in preschool-age children with autism spectrum disorders (ASD); the relationships between sensory processing and problem behavior, adaptive behavior, and cognitive function; and the differences in sensory processing between two subgroups (autism and pervasive developmental disorder-not otherwise specified). RESULTS. Most of the children with ASD had sensory processing challenges, and a significant relationship was found between SSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 28 publications
6
74
1
4
Order By: Relevance
“…It seems that parents mainly considered their child's challenging behaviors such as tantrumming and inability to stay focused and follow teacher's instructions as factors that cause academic skills issues. In fact, these challenging behaviors have been widely reported among children with ASD (Ashburner et al 2008;Ben-Sasson et al 2009;O'Donnell et al 2012;Schaaf et al 2011;Tomchek & Dunn 2007) and have been found to affect academic achievement among these children (Ashburner et al 2008). It should also be noted that none of the parents involved in this study mentioned any concerns regarding their child's ability to perform basic academic skills such as holding a pencil; recognizing alphabets, numbers and shapes; and being able to read.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It seems that parents mainly considered their child's challenging behaviors such as tantrumming and inability to stay focused and follow teacher's instructions as factors that cause academic skills issues. In fact, these challenging behaviors have been widely reported among children with ASD (Ashburner et al 2008;Ben-Sasson et al 2009;O'Donnell et al 2012;Schaaf et al 2011;Tomchek & Dunn 2007) and have been found to affect academic achievement among these children (Ashburner et al 2008). It should also be noted that none of the parents involved in this study mentioned any concerns regarding their child's ability to perform basic academic skills such as holding a pencil; recognizing alphabets, numbers and shapes; and being able to read.…”
Section: Discussionmentioning
confidence: 73%
“…Efforts in managing problems faced by children with ASD and their families need to be appropriately channeled, so that problems of not being able to fully and actively participate in their life and community settings could be adequately addressed (Rodger & Umaibalan 2011;Spann et al 2003) According to a published preliminary study, there is generally low public awareness on the difficulties faced by children with ASD in Malaysia, with some participants having never heard of the condition (Md Shamsudin & Abdul Rahman 2014). This ignorance would help to explain the negative reaction and stigmatization placed on children with ASD and their families (Gray 1993;Woodgate et al 2008), specifically, on those who exhibit challenging behaviors (Ashburner et al 2008;O'Donnell et al 2012;Schaaf et al 2011). This stigmatization could increase psychological stress in parents or caregivers of children with ASD (Schaaf et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The behaviours themselves -which range from a fear of hairdryers to a fascination with twinkling lightshave been shown to occur in a large proportion of autistic 1 individuals, across sensory modalities (Ben-Sasson et al, 2009) and across ages (Crane et al, 2009), intellectual abilities and autism severity (Ben-Sasson et al, 2009;Crane et al, 2009;Hochhauser & Engel-Yeger, 2010). Empirical links between sensory atypicalities and behavioural difficulties (Baker, Lane, Angley, & Young, 2008;O'Donnell, Deitz, Kartin, Nalty, & Dawson, 2012), academic achievement (Ashburner, Ziviani, & Rodger, 2008) and anxiety and depression (Green, Ben-Sasson, Soto, & Carter, 2012;Mazurek et al, 2012) point to the often-debilitating impact that sensory difficulties can have on individuals' daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these core diagnostic features, it has been documented that children with ASD are more likely to exhibit sensory differences, such as overresponding or underresponding to sensory input, that negatively impact their participation in activities of daily living, community participation, and family quality of life (Bagby, Dickie, & Baranek, 2012;O'Donnell, Deitz, Kartin, Nalty, & Dawson, 2012;Tomchek & Dunn, 2007). and found a significant (p < .001) relationship between the degree of sensory processing impairments and behavior challenges, including irritability, lethargy, stereotypic behavior, hyperactivity, and inappropriate speech.…”
mentioning
confidence: 99%